Polyurethane nanofiber strain sensors via in situ polymerization of polypyrrole and application to monitoring joint flexion - Kim, Inhwan; Cho, Gilsoo (Smart materials and structures, 2018)
Strain sensors made of intrinsically conductive polymers (ICPs) and nanofibers were fabricated and tested for suitability for use in wearable technology. The sensors were fabricated and evaluated based on their surface appearances, and electrical, tensile, and chemical/thermal properties. Polypyrrole (PPy) was in situ polymerized onto polyurethane (PU) nanofiber substrates by exposing pyrrole monomers to ammonium persulfate as oxidant and 2,6-naphthalenedisulfonic acid disodium salt as doping agents in an aqueous bath. The PPy treated PU nanofibers were then coated with polydimethylsiloxane (PDMS). Both pyrrole concentrations and layer numbers were significantly related to change in electrical conductivity. Specimen treated with 0.1 M of PPy and having three layered structure showed the best electrical conductivity. Regarding tensile strength, the in situ polymerization process decreased tensile strength because the oxidant chemically degraded the PU fibers. Adding layers and PDMS treatment generally improved tensile properties while adding layers created fracture parts in the stress-strain curves. The treatment condition of 0.1 M of PPy, two layered, and PDMS treated specimen showed the best tensile properties as a strain sensor. The chemical property evaluation with Fourier transform infrared and x-ray photoelectron spectroscopy tests showed successful PPy polymerization and PDMS treatments. The functional groups and chemical bonds in polyol, urethane linkage, backbone ring structure in PPy, silicon-based functional groups in PDMS, and elemental content changes by treatment at each stage were characterized. The real-time data acquired from the dummy and five human subjects with repetition of motion at three different speeds of 0.16, 0.25 and 0.5 Hz generated similar trends and tendencies. The PU nanofiber sensors based on PPy and PDMS treatments in this study point to the possibility of developing textiles based wearable strain sensors developed using ICPs.